IκBNS-deficiency protects mice from fatal Listeria monocytogenes infection by blunting pro-inflammatory signature in Ly6Chigh monocytes and preventing exaggerated innate immune responses - Frentzel, Sarah; Jeron, Andreas; Pausder, Alexander; Kershaw, Olivia; Volckmar, Julia; Schmitz, Ingo; Bruder, Dunja (Frontiers in Immunology, 2022)
IκB proteins regulate the inhibition and activation of NF-κB transcription factor complexes. While classical IκB proteins keep NF-κB complexes inactive in the cytoplasm, atypical IκB proteins act on activated NF-κB complexes located in the nucleus. Most of the knowledge regarding the function of IκB proteins has been collected in vitro, while far less is known regarding their impact on activation and regulation of immune responses during in vivo infections. Combining in vivo Listeria monocytogenes (Lm) infection with comparative ex vivo transcriptional profiling of the hepatic response to the pathogen we observed that in contrast to wild type mice that mounted a robust inflammatory response, IκBNS-deficiency was generally associated with a transcriptional repression of innate immune responses. Whole tissue transcriptomics revealed a pronounced IκBNS-dependent reduction of myeloid cell-associated transcripts in the liver together with an exceptionally high Nfkbid promoter activity uncovered in Ly6Chigh inflammatory monocytes prompted us to further characterized the specific contribution of IκBNS in the inflammatory response of monocytes to the infectious agent. Indeed, Ly6Chigh monocytes primed during Lm infection in the absence of IκBNS displayed a blunted response compared to wild type-derived Ly6Chigh monocytes as evidenced by the reduced early expression of hallmark transcripts of monocyte-driven inflammation such as Il-6, Nos2 and Il1-beta. Strikingly, altered monocyte activation in IκBNS-deficient mice was associated with an exceptional resistance against Lm infection and protection was associated with a strong reduction in immunopathology in Lm target organs. Of note, mice lacking IκBNS exclusively in myeloid cells failed to resist Lm infection, indicating that the observed effect was not monocyte intrinsic but monocyte extrinsic. While serum cytokine-profiling did not discover obvious differences between wild type and IκBNS-/- mice for most of the analyzed mediators, IL-10 was virtually undetectable in IκBNS-deficient mice, both in the steady state and following Lm infection. Together, we show here a crucial role for IκBNS during Lm infection with IκBNS-deficient mice showing an overall blunted pro-inflammatory immune response attributed to a reduced pro-inflammatory signature in Ly6Chigh monocytes. Reduced immunopathology and complete protection of mice against an otherwise lethal Lm infection identified IκBNS as molecular driver of inflammation in listeriosis.